Handling the difficult employee : solving performance problems - Brounstein, Marty (Crisp Pub. Menlo ParkUS, 1993)
Identifies six degrees of difficult employees and labels them in ascending order as follows: new, inconsistent, unbalanced, mediocre, marginal, and intolerable. Shows how to determine the causes of employee performance problems, and indicates what intervention steps to take. Encourages managers to give employees constructive feedback as this would improve work ethic and morale.